2021
DOI: 10.1093/jbcr/irab091
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Experiences at a Swedish National Burn Centre

Abstract: Introduction Previous studies have shown that burn patients were satisfied with the received care. Satisfaction was not strongly associated to burns or to psycho-social characteristics, suggesting that other factors, related to burn care specific aspects, may be important. The aim of this study was to analyse the independent effect of provided workload on the general satisfaction in adult patients at a Swedish national Burn Centre. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…in Iran self-immolation was estimated at 16% of hospitalised burns (Saadati et al, 2019), while another study indicated that 27% of suicide cases in Iran were via self-immolation of those, 71% were female (Ahmadi et al, 2008). Although the self-immolation rate in Iraq is significantly higher than other western countries such as Greece, representing 3.69% (Tsati et al, 2005), Sweden at 3% (Pompermaier et al, 2019), Portugal at 5% (Vieira et al, 2020), Finland at 5.7% (Palmu et al, 2004), as well as reported 17.4% of eastern Mediterranean regions (Morovatdar et al, 2013). However, self-immolation is rarely reported in western countries and is more frequent in developing regions, the Middle East and Africa (Amadasi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…in Iran self-immolation was estimated at 16% of hospitalised burns (Saadati et al, 2019), while another study indicated that 27% of suicide cases in Iran were via self-immolation of those, 71% were female (Ahmadi et al, 2008). Although the self-immolation rate in Iraq is significantly higher than other western countries such as Greece, representing 3.69% (Tsati et al, 2005), Sweden at 3% (Pompermaier et al, 2019), Portugal at 5% (Vieira et al, 2020), Finland at 5.7% (Palmu et al, 2004), as well as reported 17.4% of eastern Mediterranean regions (Morovatdar et al, 2013). However, self-immolation is rarely reported in western countries and is more frequent in developing regions, the Middle East and Africa (Amadasi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%